EFEKTIVITAS PEMERINTAH DALAM PENATAAN PEDAGANG KAKI LIMA DI KOTA PEKANBARU TAHUN 2022-2023 - Nandini, Atikah; Febrina, Rury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The presence of street vendors continues to increase amidst the activities of Pekanbaru City as a trading center in the Sumatra region. This is a matter of concern because its existence is not well organized. Therefore, further efforts are needed from the Pekanbaru City government to regulate the existence of street vendors effectively through structuring activities. Structuring street vendors is an effort carried out through determining target locations to determine, move, control and eliminate street vendor locations by paying attention to public interest, social, aesthetic, health, economic, security, order, environmental cleanliness and in accordance with statutory regulations. The arrangement of street vendors aims to provide business opportunities for street vendors by determining locations that suit their purpose. This research intends to describe the effectiveness of government in managing street vendors in Pekanbaru City. The research location is in Pekanbaru City, specifically at the Pekanbaru City Trade and Industry Office and Simpang Baru Market Pekanbaru City. This research uses the effectiveness theory put forward by Campbell. Using a descriptive qualitative approach. Data collection techniques through interviews and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this research show that based on theoretical indicators, the government’s effectiveness in managing street vendors includes the concept of program success which has not yet achieved the target of the Pekanbaru City Trade and Industry Service in restoring the function of roads as public roads. Then the success of the target has been quite effective, seen from the capacity which is almost fulfilled by street vendors. Then satisfaction with the program cannot be said to be effective, seen from the market community satisfaction index (IKM) which has not yet reached the target. At the input and output level, it is quite effective where the government has been able to produce output based on existing input. Finally, the achievement of the overall goal has not been fully effective, seen from street vendors who still violate many rules, inaccurate data and weak coordination with related agencies. Of these indicators, only two indicators can be said to be effective for government in implementing the regulation of street vendors in Pekanbaru City in 2022-2023, namely the success of targets and the level of input and output.